Efficacy of combined antioxidant therapy in male subfertility-A systematic review and meta-analysis - Arhin, Samuel Kofi; Ocansey, Stephen; Barnes, Precious; Botchey, Collins Paa Kwesi; Taylor-Adbulai, Hannah Benedicta (Cellular and Molecular Biology, 2022)
Antioxidant therapy is a potentially promising approach to improve clinical outcomes for couples undergoing assisted reproduction techniques long-term. The review aims to (a) collate evidence for the effectiveness of combined oral antioxidant supplementation, including a head-to-head comparison in the treatment of male subfertility, and (b) investigate whether other intervention features, including duration, specific combinations, or dosage affect clinical outcomes in this population. Randomized controlled trials (RCTs) that examined the effectiveness of combined antioxidants on male subfertility, electronic databases including PubMed, Embase, CINAHL, PSYCHINFO, and Cochrane Central Register of Controlled Trials (CENTRAL) were searched. We also searched for unpublished data and references of identified articles. Two reviewers screened eligible studies according to pre-defined criteria and relevant data extracted. The Jadad scale assessed the quality of studies. The study used RevMan version 5.4.1 Meta-analysis software to analyze the effect of combination antioxidants for each outcome measure. Metadata was presented as relative risks for dichotomous outcomes and as standardized mean differences (or mean differences) for continuous outcomes. The systematic review and meta-analysis aimed to report available evidence of whether combination antioxidant is effective and safe in sub-fertile men undergoing assisted reproductive techniques. Also, this review highlighted whether any specific oral antioxidant combinations, dosage, or duration of therapy have a major influence on the clinical outcomes.